ANALYSIS OF EDUCATIONAL INSTITUTION DEVELOPMENT WITH HARRISON'S OPEN-SYSTEM MODEL - Syuryatman Desri; Satria Efandi Efandi; Masdalena - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This study aims to identify and diagnose the performance of educational institutions, namely the X Foundation. This study uses a qualitative research method using the framework of the Open-System theory model from Harrison. The Open-System model is used to understand how the organization processes and interacts with the surrounding environment which also influences work processes within the organization. The data collection instruments used were interviews, field observations, document studies and surveys of Foundation employees. Based on the results of the diagnosis and analysis, it was found that the management and work systems at X Foundation were not effective enough to carry out so that their work results were less than optimal due to the ineffective management of human resources. The intervention plan that is offered is to create a process flow for compiling competencies so that the quality of performance of X Foundation’s human resources can support the achievement of the institution's vision and mission.